On “suspended” embryo (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The paper, which starts from a survey of the legislative and jurisprudential factors that over time have contributed to fueling the use of cryopreservation of residual embryos following a treatment of PMA, questions the possible fate of these, proposing a diversification of use due to their continuing suitability for implantation for procreative purposes, or the presence in them of pathological conditions impeding this.
Keywords: Cryopreservation; cryopreserved embryos; embryo donation; embryo adoption; embryo experimentation